2011
DOI: 10.1111/j.1464-410x.2011.10623.x
|View full text |Cite
|
Sign up to set email alerts
|

Overactive bladder syndrome: an underestimated long‐term problem after treatment of patients with localized prostate cancer?

Abstract: Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? In this study we observed courses of micturition symptoms and differentiated degrees of symptoms for each point in time while also considering the impact of bothersomeness. Our data show that not only significantly more patients who have undergone BT suffer from OAB than those who have undergone RP, but also that those affected show significantly higher values for severity of OAB symptoms throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 32 publications
0
40
0
1
Order By: Relevance
“…Studies have shown that urodynamic investigation identifies the aetiology of lower urinary tract dysfunction in these patients; however, the value in predicting the effects of subsequent treatment is unknown [60]. …”
Section: Urodynamic Testingmentioning
confidence: 99%
“…Studies have shown that urodynamic investigation identifies the aetiology of lower urinary tract dysfunction in these patients; however, the value in predicting the effects of subsequent treatment is unknown [60]. …”
Section: Urodynamic Testingmentioning
confidence: 99%
“…To diagnose this problem, a history of UI with certain body positions should be noted or careful evaluation of control-pump techniques should be undertaken. Patients should be taught how to completely deflate the cuff and De novo overactive bladder is not common in patients after radical prostatectomy compared with patients with an enlarged and obstructive prostate gland [10]. Most men with BPH develop a degree of overactive bladder secondary to chronic bladder adaptive changes.…”
Section: Improper Operation Of Aus Devicementioning
confidence: 99%
“…Persistent overactive bladder seems to be an underestimated problem after treatment for localized prostate cancer, especially in patients treated with brachytherapy 13. In a diabetes center in Taiwan, in which all patients were screened, 22.5% had overactive bladder, and 48.0% of those with overactive bladder had incontinence 14…”
Section: Definitions and Epidemiologymentioning
confidence: 99%